East African odontopygid millipedes 2: A new, geographically disjunct species of Chaleponcus (Attems 1914) from the Pare Mts., Tanzania (Diplopoda, Spirostreptida, Odontopygidae) - Frederiksen, Sara B. (Zootaxa, 2013)
Chaleponcus parensis n. sp.,, found in the North Pare Mountains, Tanzania, is described. The find is remarkable due to its geographically disjunct location, being at least 1500 km as the crow flies to the nearest valid record in Zimbabwe of a Chaleponcus.